The holistic living / Emily Jothee Mathai - Mathai, Emily Jothee (Academy of Language Studies, 2024)
Holistic living simply means caring for all parts of our body , be it mind , body , or soul . In our busy day - to - day lives , we often have no time to look into our overall self , which is very important for our overall well - being . Concerns crop up only when we encounter some health issues . We then rush to get then ecessary help to combat the disturbance that has affected our daily lives . Once battled , we blissfully revert to the normal routine . This way of living is unhealthy and results in many health issues in the future . In holistic living , we observe the three parts of ourselves : mind , body , and soul . All three elements are connected . Often , we tend to exertour body to complete an important task . As a result , we don’t get propers leep (body) as we are anxious (mind) of the pending work . We then practice withdrawal syndrome from family and friends (soul) to accomplish unaccomplished tasks.